RISE: Gait recognition system for mass surveillance / Dr Fakhrul Hazman Yusoff - Yusoff, Fakhrul Hazman (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
The need for surveillance and counter-terrorism mechanisms among the general public has become increasingly important in today's world, where human movement is seamless, and potential threats can exist anywhere at any time.